(untitled) (Bangladesh Journal of Pharmacology, 2016)
The study was aimed to validate the traditional uses of Polypodium vulgare in disorders associated with smooth muscle contraction and to describe its possible underlying mechanism(s) by using in vitro and in vivo experimental techniques. Rhizomes extract of P. vulgare reversed the high K+ (80 mM) and carbachol (1 µM) mediated contractions in isolated rabbit jejunum (5 and 10 mg/mL), trachea (5 and 10 mg/mL) and urinary bladder (3 and 10 mg/mL), with higher potency against carbachol than high K+, similar to dicyclomine. A rightward shift in carbachol cumulative response curves was observed in the presence of crude extract (1-3 mg/mL), similar to dicyclomine. Crude extract exhibited a dose-dependent (300-500 mg/kg) protective effect against castor oil-induced diarrhea in mice. Presence of dual blacked mechanism behind the smooth muscles relaxant effect of the crude extract, unveil medicinal significance of P. vulgare in GIT, respiratory and urinary bladder disorders. Video Clip of Methodology: Tissue preparation: 3 min 5 sec Full Screen Alternate